Perfil dos estudantes atendidos pela Clínica de Psicologia em Universidade Pública de Região de Fronteira, durante o período da pandemia do COVID-19 - Steinmetz, Lígia Angélica Radis (2024)
The COVID-19 pandemic has affected the lives of everyone, mainly university students, increasing suffering and mental health issues. This study was driven in a Psychology Clinic at a Public University in a border region. The objective was to perform an analysis of the epidemiological profile, with a clinical and socio-economic focus, of the individuals assisted at the Psychology Clinic of Unioeste – Foz do Iguaçu campus, during the COVID-19 pandemic. It is characterized as a descriptive exploratory study, developed in two stages: a systematic literature review and field research. The literature review aimed to identify knowledge gaps on the topic, providing a basis for initial discussion and expanding understanding of the issues found in both the field research and literature review. This includes understanding the main clinical conditions of suffering and mental health issues and how the pandemic may have affected these university students. The field research analyzed 118 records, revealing a profile of young adults, predominantly female (78.81%), Brazilians, living with their families, financially dependent, without children, with a prevalence of anxiety symptoms (90.68%), depression (44.91%), and grief (22.03%). The literature review demonstrated the impacts of the COVID-19 pandemic on the mental health of university students, revealing concerning prevalences of anxiety, stress, and depression. Risk factors identified included financial implications, social isolation, online learning, and concerns about the future. As the literature review as the reality found in the school clinic in Foz do Iguaçu showed changes in teaching and learning strategies during the pandemic, as well as in psychological care, despite the transition to online services. Specifically, at Unioeste, the surveyed students expressed a preference for in-person counseling, seeking support, particularly for anxiety, stress, and depression related to interpersonal, academic, and financial challenges. The study emphasizes the importance of environmental factors in the manifestation of mental disorders, highlighting changes in academic routines and responsibilities. The use of psychotropic medications and psychoactive substances was observed, denoting the need for further research. Together, the literature review and the research underscore the importance of specific interventions to address the substantial impact on the mental health of university students. The ongoing need for psychological support and institutional strategies is evident, recognizing and addressing the diverse emotional demands of students to promote a healthier and more inclusive academic environment.